Penentuan Tarif Pengiriman Kargo Menggunakan Metode Biaya Operasional Kendaraan Pada PT.XYZ - Vicky, Agnes (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT. XYZ is a company engaged in the transportation and logistics sector. One of PT. XYZ’s business operations focuses on cargo delivery services. However, the company has not yet established an official cargo delivery tariff. The accuracy of tariff determination is a crucial element in making decisions for the company’s growth. Errors in setting the tariff can have fatal consequences for the company: if the tariff is set too high, customers may switch to competitors; on the other hand, if the tariff is set too low, the company may suffer losses. This study aims to determine cargo delivery tariffs using the vehicle operational cost method at PT. XYZ. The vehicle operational cost method can be applied to set tariffs with the goal of generating profit. The research results show that there are nine round-trip cargo delivery routes, namely: Makassar ↔ Bone: Rp. 564/kg, Bone ↔ Parepare: Rp. 626/kg, Bone ↔ Wonomulyo: Rp. 679/kg, Makassar ↔ Bulukumba: Rp. 533/kg, Bulukumba ↔ Sengkang: Rp. 672/kg, Makassar ↔ Sengkang: Rp. 568/kg, Makassar ↔ Parepare: Rp. 540/kg, Makassar ↔ Pinrang: Rp. 554/kg, Makassar ↔ Palu: Rp. 1,407/kg